THE ROLE OF FORIEGN LANGUAGES IN ENHANCING CROSS CULTURAL UNDERSTANDING - Ne’matullayeva Sevinch Komiljon qizi; Hazratqulova E’zoza Ismat qizi (TADQIQOTLAR.UZ, 2024)
ABSTRACT: Foreign languages play a pivotal role in fostering intercultural understanding  by  bridging  cultural  gaps  and  enhancing  communication  between diverse groups. Learning a foreign language goes beyond linguistic skills; it enables individuals to grasp cultural nuances, promoting empathy and  mutual respect. This paper  explores  how  foreign  language  education  contributes  to  intercultural understanding,  emphasizing  the  interplay  of  language,  culture,  and  identity.  By analyzing  relevant  studies,  it  demonstrates  how  language  learners  develop  cultural competence, which facilitates effective cross-cultural interactions.